Sosialisasi Rempah Sebagai Komoditas Ekspor Rempah Melalui Media Sosial - Witri Elvianti (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Abstract Indonesia has long been known as a producer of various and high-quality spices. Although the export of spices in the form of raw materials has increased, the growth rate of export of Indonesian spice products is still lower than the volume of imports from 2013 to 2017. The percentage of Indonesian spice imports even reached 30% per year while export growth was only in the range of 8% per year. However, this is inversely proportional to the benefits that is still not maximized. Spice commodities and strengthening export growth must receive systematic and comprehensive support. Increasing public awareness about the importance of the national economy needs to be done through a cross-sectoral approach, especially the empowerment of the spice economy. This study aims to find out how the contribution to strengthening the economic potential of spices can be gained by socializing knowledge about the spice economy aimed at the community, especially the millennial generation and generation Z, which was carried out through social media campaign and online seminar.